The Acceleration of Inclusive Economic Growth in Banten - Zuhaifah Zuhaifah; Dwi Budi Santoso; Farah Wulandari Pangestuty (Journal of International Conference Proceedings (JICP), 2022)
The aim of this study is to identify the determinant of inclusive economic growth in Banten Province based on the Three Stages Least Squares (3SLS) method using panel data from 8 regency/municipality during 2011-2020 (except 2016). The results show that the government’s role through capital expenditure doesn’t have a significant effect on inclusive economic growth directly but it has an indirect effect through increasing economic activity and decreasing the unemployment rate. Based on regional financial performances, there is only the Audit Board’s opinion that has a significant positive effect on inclusive economic growth, while the independence ratio and effectiveness ratio have no effect. In accelerating inclusive economic growth in Banten, the local government has to increase economic growth and reduce the unemployment rate. The number of labor and higher education labor positively impact economic activity, while high investment can reduce the unemployment rate. However, Banten’s economy is capital intensive. Hence, the equitable distribution of appropriate capital expenditure allocations to support labor-intensive investment needs to be improved, besides enhancing the caliber of human resources and regional financial performances. Keywords: Banten, Economic Growth, Inclusive Economic Growth, Three Stages Least Squares, Unemployment